Cooperation or Non-Cooperation: A Bargaining Game Model to Make Dominant Coalition - Hadadian, Zagross; Malekpour, Sanaz (European Journal of Sustainable Development, 2018)
The concept of coalition is central to classic and recent organizational theory. This paper focuses on study of organizational coalition by using Bargaining Game Model. Players in the model are carrying on an intensive competition to maximize their utility. We study the game between two players based on Nash Bargaining game theory. We propose a game theoretical framework that shows how the players of the game determine the optimal strategy to cooperate or not cooperate in a coalition. Moreover, the influences of cooperation costs and betrayal incomes in the cooperation strategies between players are analyzed. The result shows that the cooperation of players has a negative relation with the cooperation costs and betrayal income; with the increase of cooperation costs and betrayal income, the players will become reluctant to cooperate. Keywords: Dominant coalition, Game theory